Analisis Pengaruh Kelengkapan Fitur dan Desain Navigasi Aplikasi Perbankan Berbasis Mobile Terhadap User Experience Nasabah Individu pada PT Bank Central Asia Tbk - Andrian Harinata; Anas Lutfi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The goal of this research was to find whether feature completeness and navigation design of mobile banking applications developed by PT Bank Central Asia Tbk have a significant impact to its individual customers' user experience. This research was conducted by using questionnaire, in which the population was all the individual customers of PT Bank Central Asia Tbk, while the sample was the 162 (one hundred and sixty-two) respondents who submitted the questionnaire. By using the multiple regression analysis and hypothesis test, it was found that both feature completeness and navigation design of mobile banking applications developed by PT Bank Central Asia Tbk have a positive and significant impact to its individual customers' user experience.